Combination therapy versus monotherapy for pulmonary arterial hypertension: a meta-analysis. Issue 4 (April 2016) - Lajoie, Annie Christine; Lauzière, Gabriel; Lega, Jean-Christophe; Lacasse, Yves; Martin, Sylvie; Simard, Serge; Bonnet, Sebastien; Provencher, Steeve
Summary: Background: Several randomised controlled studies and a previous meta-analysis have reported conflicting results regarding the effect of combined targeted therapy compared with monotherapy for pulmonary arterial hypertension (PAH). We did a systematic review and meta-analysis to assess the effects of a combination of PAH-specific therapies compared with monotherapy on predefined clinical worsening in PAH. Methods: We searched MEDLINE, Embase, and the Cochrane Library for reports published from Jan 1, 1990, to May 31, 2015, of prospective randomised controlled trials of at least 12 weeks that assessed a combination of PAH-specific therapies (upfront and sequential add-on) compared with background PAH-specific monotherapy in patients older than 12 years. We extracted data from the reports, and assessed the primary outcome of risk of clinical worsening, as defined a priori in each trial, using the Mantel-Haenszel method based on a fixed-effects model. Findings: Of 2017 studies that we identified from our search, we included 17 (4095 patients) in our analysis. 15 studies assessed clinical worsening and were included in the primary analysis. Combined therapy was associated with significant risk reduction for clinical worsening compared with monotherapy (combined therapy 17% [332 of 1940 patients] vs monotherapy 28% [517 of 1862 patients], risk ratio [RR] 0·65 [95% CI 0·58–0·72], p<0·00001). We noted no heterogeneity between the studies ( I 2 =18%, phomogeneity =0·25). A publication bias was suggested by the results of an Egger test ( t =–2·3982, p=0·031), but when we excluded the four studies with the highest SEs, the RR for clinical worsening was identical (0·65 [95% CI 0·58–0·73], p<0·00001). Interpretation: In our analysis, combined therapy for PAH was associated with a significant reduction in clinical worsening compared with monotherapy. However, our study was limited by the variable definition of clinical worsening among the trials and possible publication bias. Because many patients still had clinical worsening with combination therapy, identification of innovative therapeutic targets for PAH is thus urgently needed. Funding: None.